Pelayanan Pengasuhan Keluarga Pengganti Bagi Anak Berhadapan Dengan Hukum Di Sentra Handayani Jakarta - Areniska Syahri; Sokhivah Sokhivah; Gwn Gwn (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to find out and describe the stages of social services in substitute family care for Children in Conflict with the Law (ABH) at the Handayani Center, Jakarta. This type of research is qualitative research with descriptive and library research methods. The main instruments in this research are caregivers or substitute family for ABH, ABH residential supervisors and assisted by supporting instruments, namely stationery, cameras, andtape recorder. Data collection techniques were carried out through interviews, observation and documentation. The steps for analyzing this research use the stages of service from Karen K. Krist Ashmen. The results of this research include social services in surrogate families for Children in Conflict with the Law (ABH) consisting of several stages, such as Information on Prospective Replacement Families, Criteria for Prospective Replacement Families, Criteria for Prospective Foster Children, Registration of Prospective Replacement Families, Interviews for Prospective Replacement Families, Selection Administrative, Technical Guidance, Home Placement for Surrogate Families, and Case Conference (CC) Meetings.